Econometrics - Baltagi, Badi H. (Springer eBooks., 2011)
This textbook teaches some of the basic econometric methods and the underlying assumptions behind them. It also includes a simple and concise treatment of more advanced topics in spatial correlation, panel data, limited dependent variables, regression diagnostics, specification testing and time series analysis. Each chapter has a set of theoretical exercises as well as empirical illustrations using real economic applications. These empirical exercises usually replicate a published article using Stata or Eviews. "A most useful text for an econometrics course. There are not many introductions to econometrics which approach the relevant material so consistently from the viewpoint of the student. The book is also well suited for self study and can be recommended to everybody who is in need to quickly acquire the basics of the field."